(untitled) (AYUSHDHARA, 2023)
Bell’s palsy is the most common form of unilateral isolated lower motor neuron type of facial palsy. This is an idiopathic condition with abrupt onset leading to weakness of one-half of the face. The present case report is on the effectiveness of Nasya Karma and Shirodhara procedures in Bell’s palsy. A 35-year-old female patient visited the OPD with complaints of deviation of the mouth, improper closure of eyes, and dribbling of saliva for four days. She was diagnosed with Bell’s palsy. Bell’s palsy can be correlated with Ardita based on clinical features. The patient was hospitalized and managed with Sthanik Snehana (localized oleation /massage therapy), Sthanik Swedana (localized steam), Nasya Karma (medicine administered through nasal route), and Shirodhara (medicated decoction/oil pouring over the forehead) along with oral Ayurvedic formulations. She got noteworthy relief in all features in two weeks. The collected data emphasize the potential of Ayurvedic interventions in Bell’s palsy (Ardita).